Potassium, calcium and magnesium nutritional requirements of sweet sorghum - Alves, Antonio Carlos; Brauner, Jorge Luis; Cordeiro, Daltro Silva; Zonta, Élio Paulo; Correa, Luís Antonio Veríssimo (Pesquisa Agropecuaria Brasileira, 2014)
A field experiment was conducted in Pelotas (1983/84), RS, Brazil, with the following objectives: (a) evaluate potassium, calcium and magnesium, mineral nutrition requirements of sweet sorghum, (b) distribution of these elements in the plant, (c) luxury consumption of K, and (d) to verify the combined effect of potassium fertilization/absorption by the crop on the available K in the soil. Four treatments of K2O (zero, 50, 100 and 150 kg/ha) were used. All plots received 120 kg/ha of N, 100 kg/ha of P2O5 and 2 t/ha of limestone at seeding time. The cultivar used was BR-501 with a stand of 140,000 plants/ha and the crop was harvested 127 days after emergence. Plants were separated into the following components: leaves, stalks, panicles and plant residues. Potassium, calcium and magnesium were determined in the samples. The following conclusions were reached: (a) to produce 60.4 t/ha of fresh stalks + leaves, 116 kg/ha of K, 54 kg/ha of Ca and 91 kg/ha of Mg are needed; (b) content of K is higher in stalks, while Ca and Mg were higher in leaves; (c) K, depending on the K2O rate, (produces) synergistic or antagonistic effects on the Ca and Mg; (d) high luxury consumption of K occurs, accumulating mainly in stalks and finally, (e) to avoid K deficiency in soil, sorghum leaves should be left in the field or incorporation of vinasse (rich in K) is recommended.